2015
DOI: 10.1016/j.jnutbio.2015.05.004
|View full text |Cite
|
Sign up to set email alerts
|

GRID and docking analyses reveal a molecular basis for flavonoid inhibition of Src family kinase activity

Abstract: Flavonoids reduce cardiovascular disease risk through anti-inflammatory, anti-coagulant and anti-platelet actions. One key flavonoid inhibitory mechanism is blocking kinase activity that drives these processes. Flavonoids attenuate activities of kinases including phosphoinositide-3-kinase, Fyn, Lyn, Src, Syk, PKC, PIM1/2, ERK, JNK and PKA. X-ray crystallographic analyses of kinase-flavonoid complexes show that flavonoid ring systems and their hydroxyl substitutions are important structural features for their b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 66 publications
(75 reference statements)
2
24
0
Order By: Relevance
“…The findings by Wright et al predict that quercetin would inhibit the activity of Src family kinases with greater potency than apigenin and catechin. This prediction was confirmed using in vitro kinase assays [ 80 ].…”
Section: Cmda Of Catechin-protein Interactionmentioning
confidence: 70%
See 1 more Smart Citation
“…The findings by Wright et al predict that quercetin would inhibit the activity of Src family kinases with greater potency than apigenin and catechin. This prediction was confirmed using in vitro kinase assays [ 80 ].…”
Section: Cmda Of Catechin-protein Interactionmentioning
confidence: 70%
“…A clearer understanding of structural interactions between flavonoids and kinases is necessary to allow the construction of more potent and selective counterparts. Wright et al examined the interactions of quercetin, apigenin and catechin with Src family kinases (Lyn, Fyn and Hck) by several methods, including CMDA, and revealed potential hydrogen bond contacts between flavonoid hydroxyls and kinase catalytic site residues [ 80 ]. Quercetin formed the most energetically stable interactions, apigenin lacked the hydroxyl groups necessary for important contacts and the non-planar structure of catechin could not support predicted hydrogen bonding patterns.…”
Section: Cmda Of Catechin-protein Interactionmentioning
confidence: 99%
“…al have shown quercetin-3glucuronide to potently inhibit protein disulphide isomerase (PDI), an oxidoreductase important in thrombus formation (80) . X-ray crystallographic analyses of flavonoid-kinase complexes have shown that flavonoid ring systems and the hydroxyl groups are important features for kinase binding (81) (82) supporting the evidence for structure-specific effects on platelet function. Taken…”
Section: Flavonoids and Platelet Aggregationmentioning
confidence: 82%
“…A protein kinase A (PKA) inhibition assay was carried to measure the potency of hesperetin and its monoglucuronides H‐7G and H‐3′G to inhibit PKA as possible mechanism underlying some of its beneficial effects . The PKA inhibition assay was carried out based on the method described by Chen et al.…”
Section: Methodsmentioning
confidence: 99%